Kajian Aspek Bio-Ekologi Ikan Sidat (Anguilla Spp.) Di Sungai Air Ngalam Kabupaten Seluma - Bendi Extra; Dede Hartono; Dewi Purnama (ACROPORA: Jurnal Ilmu Kelautan dan Perikanan Papua, 2020)
Eel (Anguilla spp.) is a fish that has a perfect tail, dorsal and anal fins. The eel's fins are equipped with visible soft fingers and the three fins are connected to each other, starting from the back to the tail and ending at the abdomen of the body. The thing that stands out from the eel is the presence of a pair of pectoral fins that are visible on both sides of the body which is located behind the head so that it is suspected that the fins are the ears. Identification of eel species is very important for the management of a resource. The ADL/% TL key character comparison is one way of identifying the types of eels that can be applied. Sampling and measurement of water parameters were carried out on 23 to 25 August 2020. From the research results obtained 1 type of eel, namely Anguilla bicolor (ADL/% TL = -0.37 to 4.76) where the eel entered the Yellow ell phase. This Anguilla bicolor eel likes slow-flowing waters (lentic waters) and sandy mud. Overall the water parameters in the Air Ngalam River are still in optimal conditions to support the survival of the eels, namely temperature 28.5 to 29.8oC, salinity 0 ppt, pH 7.1 to 7.4, brightness 96.48%, and flow velocity 23.78 cm/s. Based on statistical tests, the typology of the Air Ngalam river affects the types of eels found.Keywords: Eel; Phase; Typology; Identification